Exploring the appropriateness of the Montreal Cognitive Assessment as a culturally sensitive screening test in the Sesotho-speaking population - Mienie, Jan Konig (University of the Free State, 2020)
Neurocognitive disorder (NCD) or dementia, is a progressive neurodegenerative syndrome that causes severe impairment in function. The disease burden of NCD is increasing in middle- and low-income countries as life expectancy increases. Early detection and intervention is essential in the management of NCD. In countries with severe resource constraints, low-cost screening tools to diagnose cognitive impairment is imperative, as extensive neurocognitive batteries are rarely feasible. The Montreal Cognitive Assessment (MoCA) is one of these screening tools designed for the diagnosis of mild cognitive impairment. Limited information on the validity of the MoCA in a South African population is available, as it was initially validated for English- and French-speaking populations. We conducted a descriptive study that explored the appropriateness of the MoCA in screening for cognitive impairment in a Sesotho-speaking population. The study was conducted in Bloemfontein in the Free State Province, South Africa. Participants were recruited from National District Hospital and Pelonomi Academic Hospital. Ninety-three Sesotho-speaking healthcare users between 18 and 62 years of age were recruited. All participants were screened for mental and other illnesses that could impair cognitive function prior to the administration of the MoCA. Using the normed MoCA cut-off score of 26. The MoCA yielded a false positive screen with a total score of 25 or less in 63 (67.7%) of the participants. Although participants with a tertiary level of education did perform better than the participants with lower educational attainment, their mean total score of 23.9 was still below the recommended cut-off score. Significant concerns regarding cultural bias in the MoCA emerged in the sample, regardless of the level of education of participants. This might indicate that some items may not be culturally appropriate for the Sesotho-speaking population and might lead to false positive screening for cognitive impairment. Future research should focus on collecting normative data in the population in an attempt to suggest more appropriate substitutes for these items.
Dissertation (M.Med. (Psychiatry))--University of the Free State, 2020
Keywords: Screening tests for dementia; Neurocognitive disorder; Montreal Cognitive Assessment; MoCA; Cognitive assessment in South Africa